KOMPETENSI LITERASI INFORMASI PUSTAKAWAN DI ERA INFODEMIK - Fatmawati, Endang (Program Studi Ilmu Perpustakaan dan Informasi, Universitas Islam Nusantara, 2020)
The purpose of writing is to bring up creative librarian ideas and provide problem-solving strategies related to the circulation of hoax in the infodemic era. The discussion uses the literature review method related to infodemics, information literacy competencies, and librarian strategies in the social media era. High rapid social media and internet access users are not accompanied by literacy competencies. One of the efforts to build a knowledge ecosystem is through increasing information literacy competencies. In the context of libraries, social media influences the relationships and social interactions carried out by librarians. The wave of information that is not necessarily accurate is increasingly being spread through social media. Library information sources can be disseminated through social media applications with various platforms. His practice in the library is building scientific communication, knowledge management, promotion, marketing, and publication. Due to the rapid dissemination of information, librarians are expected to have the sensitivity and expertise in packaging information, disseminating it through social media, cleverly sorting and choosing, and wisely using it. The problem-solving strategy that exists in the era of social media for librarians to be able to surf the internet is healthy information literacy competence.Keyword: information literacy, librarian competence, hoax, infodemic, social mediaABSTRAKTujuan penulisan untuk memunculkan gagasan kreatif pustakawan dan memberikan strategi pemecahan masalah terkait dengan beredarnya informasi hoaks di era infodemik. Metode kajian menggunakan metode kajian pustaka terkait dengan infodemik dalam era media sosial, kompetensi literasi informasi, serta strategi pustakawan di era media sosial. Tingginya akses internet dan pesatnya pengguna aktif media sosial tidak dibarengi dengan kompetensi literasi. Padahal salah satu upaya membangun ekosistem pengetahuan adalah melalui peningkatan kompetensi literasi informasi. Dalam konteks perpustakaan, media sosial berpengaruh pada relasi dan cara berinteraksi sosial yang dilakukan oleh pustakawan. Gelombang informasi yang belum tentu akurat semakin terasa masif penyebarannya melalui media sosial. Sumber informasi perpustakaan dapat didesiminasikan melalui aplikasi media sosial dengan berbagai platform. Praktiknya di perpustakaan adalah membangun komunikasi ilmiah, pengelolaan pengetahuan, promosi, pemasaran, serta publikasi. Oleh karena penyebaran informasi demikian pesat, maka pustakawan diharapkan memiliki kepekaan dan kepiawaian dalam mengemas informasi, menyebarkan melalui media sosial, cerdas memilah dan memilih, maupun bijak dalam menggunakannya. Strategi pemecahan masalah yang ada di era media sosial bagi pustakawan agar dapat berinternet sehat adalah memiliki kompetensi literasi informasi.